Dynamic balance performance and noncontact lower extremity injury in college football players: An initial study - Butler, R. J.; Lehr, M. E.; Fink, M. L.; Kiesel, K. B.; Plisky, P. J. (Sports Health: A Multidisciplinary Approach, 2013)
Background: Field expedient screening tools that can identify individuals at an elevated risk for injury are needed to minimize time loss in American football players. Previous research has suggested that poor dynamic balance may be associated with an elevated risk for injury in athletes; however, this has yet to be examined in college football players.